TRADE-OFF ANALYSIS OF ECONOMIC GROWTH AND AIR POLLUTION EFFECTING DECREASE OF POOR ENVIRONMENTAL QUALITY IN SUMATERA UTARA PROVINCE - Benni Sinaga; Zahari Zein (Quantitative Economics Journal, 2019)
The development of economic activities will certainly have a positive impact on increasing economic growth and also have a negative impact on pollution each year, will certainly affect the quality of the environment in the province of North Sumatera . This study aims to analyze the relationship and influence of the GDP, water pollution, air pollution and soil contamination on environmental quality in North Sumatera  province both simultaneously and partially. The data used are secondary data from BPS Sumatera  and North Sumatera  Environmental Agency in the form of time series data from 2004 to 2014. Correlation analysis using correlation with SPSS version 20. Results of correlation coefficient analysis in this study explains that economic growth (0.945), water pollution (0.969), air pollution (0.903) have the relationship is very strong, while soil contamination ( 0.803) have a strong closeness with the quality of the environment in the province of North Sumatera . The results also showed that the variables of economic growth, pollution of water, air and soil are able to explain a model of environmental quality in North Sumatera  province at 96.8 percent.